Assessment of Using Inertial Profilers to Measure Ride Quality on Short Projects. Issue 1 (2017) - Kouchaki, Sareh; Prozzi, Jorge A.; de Fortier Smit, Andre; Buddhavarapu, Prasad
The Texas Department of Transportation (DOT) ride standard specifies two devices for measuring ride quality on pavement projects: the 10-ft (3-m) straightedge and the inertial profiler. According to this specification, inertial profilers measure the ride quality on projects longer than 2, 500 ft (762 m). The 10-ft straightedge must be used to survey roughness for projects of less than 2, 500 ft. A study was conducted to identify the potential issues associated with the use of inertial profilers and the international roughness index (IRI) algorithm on short projects. A literature review was performed to collect required information about the inertial profiler operation and the IRI algorithm. A field experiment was conducted with an inertial profiler certified by the Texas DOT. The collected data were analyzed to investigate the effect of profiling speed and segment length. The results indicate that inertial profilers can be used to collect profile data on short segments of less than 2, 500 ft, but the IRI algorithm should be used on projects longer than 528 ft (161 m), below which the variation between IRI results increases significantly.